2019
DOI: 10.1038/s41564-019-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated glycosaminoglycans and low-density lipoprotein receptor contribute to Clostridium difficile toxin A entry into cells

Abstract: Clostridium difficile toxin A (TcdA) is a major exotoxin contributing to disruption of the colonic epithelium during C. difficile infection. TcdA contains a carbohydrate-binding CROPs (combined repetitive oligopeptides) domain that mediates its attachment to cell surfaces, but recent data suggest the existence of CROPs-independent receptors. Here we carried out genome-wide CRISPR-Cas9-mediated screens using a truncated TcdA lacking the CROPs and identified sulfated glycosaminoglycans (sGAGs) and low-density li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 51 publications
3
92
0
Order By: Relevance
“…As a control, also binding of labeled Clostridium difficile toxin A (TcdA) was studied. It was recently shown that TcdA binds to sulfated GAG (14). In the presence of heparin, hyaluronic acid and dextran sulfate, respectively, there was reduced binding of TcdA to Hela cells ( Fig.…”
Section: Identification Of the Relevant Gagmentioning
confidence: 79%
See 2 more Smart Citations
“…As a control, also binding of labeled Clostridium difficile toxin A (TcdA) was studied. It was recently shown that TcdA binds to sulfated GAG (14). In the presence of heparin, hyaluronic acid and dextran sulfate, respectively, there was reduced binding of TcdA to Hela cells ( Fig.…”
Section: Identification Of the Relevant Gagmentioning
confidence: 79%
“…This is in contrast to the recently proposed binding of the clostridial toxin TcdA to the cell surface. The authors could interfere with intoxication of cells by addition of surfen (14). HSPGs are extracellular matrix components (27), they are found in secreted vesicles of mast cells (serglycin, (28)), described as sequestering co-receptors for growth factors and cytokines (fibroblast growth factor (FGF), (29,30)) or binding partners for molecules undergoing transcellular transport (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, despite high sequence similarity between TcsL and TcdB, our screen did not identify Frizzled receptors, or CSPG4 or PVRL3, two other TcdB-associated receptors (7,10,11). Neither did we identify known receptors for C. perfringens TpeL or C. difficile TcdA, other related LCTs (12,13), although all these receptors are expressed in Hap1 cells ( fig. S1B).…”
mentioning
confidence: 69%
“…We cannot exclude the possibility that, like other clostridial toxins (7,(10)(11)(12), TcsL also binds additional receptors on host cells. However, we did not identify additional factors in CRISPR/Cas9 screens in cells that do not express SEMA6A or SEMA6B.…”
Section: Figure 2 Sema6a Ectodomain Protects Lung Endothelial Cells mentioning
confidence: 99%